Estudio de prefactibilidad para la instalación de una planta productora de tablones de madera de pino (Pinus radiata) - Eyzaguirre Dias, Gonzalo Jesus (2016)
This study has the objective to determine the feasibility of the development of a pine tree sawmill instalation. The project has an initial market, technic and social justification, based in the existence of a growing market, an stablished production process and the potential to generate new work positions and enviromental benefits. The proposed product consists in pine wood planks. The main target market for this products consists of furnitures manufacturers located in Lima Sur, particulary Villa El Salvador. The demand was proyected and segmentated in orden to determine an initial project demand of 8.908 m3 in 2016 with an anual growth of 8.7% until 2023. The sawmill should be located in Cajamarca ditrict, which was determined through a macro localization and micro locatization methodologies. Main advantages of Cajamarca are proximity to pine plantations, access to highway and available supply of wáter and electrical power. Relationships size-market, size-raw material, size-technology and size breakeven were analized to define a sawmill size of 15.951 m3 in 2023. A capacity of 16.981 m3/year was calculated for 2023, based in a detailed bottle neck analysis of process by process. To determine technical feasibilidy, an engineering study was made. It consisten in detting detailed specifications of the end product, design a detailed production process and select the equipments required for each stage of the process. Finally, a relational analysis between áreas was made, and the optimal plant desing was made throgh Guerchet methodology. The investment required for the project is PEN 8.488.600, which will be 69% financed with equity and 31% with and bank loan. Economic NPV of the project was calculated at PEN 12.384.263 and financial NPV was calculated at PEN 11.127.717, showing financial feasibility of the project.